Use of frameless intrauterine devices and systems in young nulliparous and adolescent women: results of a multicenter study - Wildemeersch D; Jandi S; Pett A; Nolte K; Hasskamp T; Vrijens M (Dove Medical Press, 2014)
Dirk Wildemeersch,1 Sohela Jandi,2 Ansgar Pett,2 Kilian Nolte,3 Thomas Hasskamp,4 Marc Vrijens5 1Gynecological Outpatient Clinic and IUD Training Center, Ghent, Belgium; 2Gynecological Outpatient Clinic, Berlin, 3Gynecological Outpatient Clinic, Uetze, 4GynMünster, Münster, Germany; 5Gynecological Outpatient Clinic, Ghent, Belgium Background: The purpose of this study was to provide additional data on the experience with frameless copper and levonorgestrel (LNG) intrauterine devices (IUDs) in nulliparous and adolescent women. Methods: Nulliparous and adolescent women, 25 years of age or younger, using the frameless copper IUD or the frameless LNG-releasing intrauterine system (IUS), were selected from previous studies and a current multicenter post-marketing study with the frameless copper IUD. The small copper-releasing GyneFix® 200 IUD consists of four copper cylinders, each 5 mm long and only 2.2 mm wide. The frameless FibroPlant® LNG-IUS consists of a fibrous delivery system releasing the hormone levonorgestrel (LNG-IUS). The main features of these intrauterine contraceptives are that they are frameless, flexible, and anchored to the fundus of the uterus. Results: One hundred and fifty-four nulliparous and adolescent women participated in the combined study. One pregnancy occurred with the GyneFix 200 IUD after unnoticed early expulsion of the device (cumulative pregnancy rate 1.1 at one year). Two further expulsions were reported, one with the GyneFix 200 IUD and the other with the FibroPlant LNG-IUS. The cumulative expulsion rate at one year was 1.1 with the copper IUD and 2.2 with the LNG-IUS. The total discontinuation rate at one year was low (3.3 and 4.3 with the copper IUD and LNG-IUS, respectively) and resulted in a high rate of continuation of use at one year (96.7 with the copper IUD and 95.7 with the LNG-IUS, respectively). Continuation rates for both frameless copper IUD and frameless LNG-IUS remained high at 3 years (>90%). There were no cases of perforations or pelvic inflammatory disease reported during or following insertion. Conclusion: This report confirms earlier studies with frameless devices and suggests that the high user continuation rate is attributable to the optimal relationship between the IUD and the uterine cavity. IUD studies have shown that an IUD that does not fit well will often lead to side effects (ie, pain, bleeding, embedment, expulsion) and subsequent removal of the IUD. Early discontinuation is not the aim of long-acting reversible contraception. Keywords: GyneFix®, FibroPlant®, frameless, intrauterine device, intrauterine system, efficacy, tolerance, continuation rate